2016
DOI: 10.1016/j.jcomdis.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Do the early development of gestures and receptive and expressive language predict language skills at 5;0 in prematurely born very-low-birth-weight children?

Abstract: After reading this article, readers will understand the associations between the very early (≤2 years of age) development of gestures and language (i.e. early receptive lexicon, expressive lexicon at 2;0, receptive and expressive language ability at 2;0) and the language skills at 5;0 in prematurely born very-low-birth-weight (VLBW) children. In addition, readers will understand the heterogeneity of the group of VLBW children. The information presented in this article is informative for those who work in a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
15
3
1
Order By: Relevance
“…To sum up, our results suggest that more evident difficulties for hearing and language development manifest at the end of the 1st year postpartum, when a baby should start to use gestures, vocalizations and single words to communicate. These findings are important because they highlight the importance of planning early language-focused interventions in order to limit these subsequent difficulties (Stolt et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…To sum up, our results suggest that more evident difficulties for hearing and language development manifest at the end of the 1st year postpartum, when a baby should start to use gestures, vocalizations and single words to communicate. These findings are important because they highlight the importance of planning early language-focused interventions in order to limit these subsequent difficulties (Stolt et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…The value of parental concern has also been examined in other studies and it has been shown to correlate with weak language test results, especially weak expressive Screening language skills at 2;0 language skills (Hayiou-Thomas, Dale & Plomin, 2014;Korpilahti et al, 2016;McLeod & Harrison, 2009). Also emotions, gaze, non-verbal communication, receptive lexical skills and the use of objects have been found to be associated with concurrent and later language skills (Laakso, Eklund & Poikkeus, 2011;Lyytinen et al, 2005;Stolt et al, 2016;Stolt, Mäkilä et al, 2014;Watt, Wetherby & Shumway, 2006;Wetherby & Prizant, 2002). These skills provide important information on very early language and communication and can be used for screening purposes (Laakso et al, 2011;Wetherby & Prizant, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…911 Performance on early language assessments is associated with language evaluations 1–3 years later. 1214 Language delays can be highly detrimental to children’s development because language plays a critical role in learning and reading. 15, 16 Understanding the underlying processes associated with language skills may elucidate causes and shape treatments of language delays.…”
mentioning
confidence: 99%